Pollutants Removal Efficiency in The Hydroponic Lagoon of The Wastewater Treatment Plant - Jakubaszek, Anita (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Wastewater treatment in semi-natural systems, such as a hydroponic lagoon operating as the third stage of treatment, is becoming more and more popular because of the efficiency of organic matter and nutrient removal. The article presents an analysis of the efficiency of pollutant removal at the mechanical-biological wastewater treatment plant in Gronów with a capacity of Qd = 1125m3/day and a load of 9375 PE. The wastewater treatment plant operates on the basis of activated sludge and biomass settling technology on submerged flow beds.
Keywords: wastewater treatment plant; wastewater treatment; hydroponic lagoon; mechanical-biological wastewater; oczyszczalnia ścieków; oczyszczanie ścieków; laguna hydroponiczna; oczyszczanie mechaniczno-biologiczne